Cognitive load mitigates the executive but not the arousal vigilance decrement - Luna, Fernando Gabriel (2022)
Previous research has shown opposite effects of dual tasking on the vigilance decrement phenomenon. We examined the executive (i.e., detecting infrequent critical signals) and arousal (i.e., sustaining a fast reaction to stimuli without much control on responses) vigilance decrements as a function of task load. Ninety-six participants performed either a single signal-detection (i.e., executive vigilance) task, a single reaction time (i.e., arousal vigilance) task, or a dual vigilance task with the same stimuli and procedure. All participants self-reported their fatigue’ state along the session. Exploratory analyses included data from a previous study with a triple task condition. Task load significantly modulated the executive but not the arousal vigilance decrement. Interestingly, the largest increase in mental fatigue was observed in the single executive vigilance task condition. We discuss limitations of classic vigilance theories to account for the vigilance decrement and changes in mental fatigue as a function of task load.